Pengaruh Islamic Corporate Social Responsibility Disclosure Terhadap Reputasi Dan Kinerja Keuangan Perusahaan - Nolita Yeni Siregar; Attya Rahmanisa (Universitas Mercu Buana, 2019)
This study examines the effect of Islamic corporate social responsibility on the company's reputation and financial performance. In this study the independent variables were tested, namely the Islamic Corporate Social Responsibility Disclosure and the dependent variable of corporate reputation and financial performance which were proxied to ROA and ROE. The population in this study are companies registered in the Jakarta Islamic Index in 2014-2016. The sampling technique used was purposive sampling, so that a sample of 18 companies could be obtained. This research was conducted in 2014-2016, so the amount of data in this study was 54 data. The analytical method used is the MANOVA TEST with the SPSS V.20 tool. The results of the study prove that the Islamic Corporate Social Responsibility Disclosure influences the company's reputation and ROE. While the Islamic Corporate Social Responsibility Disclosure does not have a significant effect on ROA.